Keragaan Tanaman Ubi Kayu Lokal Bangka dengan Pemberian Mikoriza di Tanah Masam - Lestari, Tri; Apriyadi, Rion; Setiawan, Fajar (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
The local cassava plant of Bangka has not been utilized optimally because its production is still low compared to national varieties. There are several ways to create good soil conditions to support plant growth in acid soils, such as the addition of mycorrhiza. The objective of the study was to increase the growth and production of Bangka local cassava in acid soils. The experiment had been conducted on acid soils with pH 4.4 (very acidic) and P-Bray 1 5.8 ppm (very low) in Balunijuk Village, Bangka Regency, from September 2016 - May 2017. This research used the experiment method with factorial randomized block design (FRBD) with two factors. The first factor was Bangka local cassava namely Sutera, Mentega, Batin, 3 Bulan and Malang variety (as the comparison) and second factor was mycorrhiza. The results showed Sutera accession had the highest plant height and production in acid soils. The addition of mycorrhiza as much as 50 g / plant can increase the growth and production of Bangka local cassava. The Bangka local cassava showed better growth quality but still have lower production compared with national varieties. Conservation of local cassava plants Bangka in acid soils can be optimized its growth by using local clones Bangka, but the production of national varieties is higher compared local cassava of Bangka